Resenha de Chi ha paura dei Greci e dei Romani? – Dialogo e cancel culture, de Maurizio Bettini. (Letras & Letras, 2024)
Resenha de Chi ha paura dei Greci e dei Romani? – Dialogo e cancel culture, de Maurizio Bettini.